موقف صحيفة اليقظة من الاصلاحات العامة في بغداد 1946-1952 - عبدالواحد عبدالنبي احمد (Al-Adab Journal, 2018)
We refer in our research about marked (Al-Yaqdha newspaper of general reforms in Baghdad from 1946 to 1952), a set of facts and incidents historical relevant social, political and economic dimension of the public and the reforms that have passed the city of Baghdad, at the stage of the monarchy, especially the clear positions of the newspaper vigilance Baghdad, which dealt with on its front page b the first political reality, general conditions in Baghdad for the period 1946-1952 placed search. The study came to include an introduction and an introduction for vigilance newspaper since its inception and then launched a major Bembages, the first section was titled (stand vigilance newspaper of general reforms in Bgdad1946-1948) with subheadings considering the positions historically vigilance newspaper Bshi detail, as follows (the position of vigilance newspaper public freedoms, the position of the newspaper vigilance of the parliamentary elections of 1947, the position of vigilance from January dart newspaper parliamentary elections of 1948). The second section came complement from a historical perspective for the period 1949-1952 entitled (stand vigilance newspaper of general reforms in Baghdad from 1949 to 1952) with branched addresses from the second topic dealt with (vigilance of the dominance of the executive over the other branches newspaper stand, stand vigilant newspaper of elections and reform of the judiciary, the position of the newspaper vigilance of the economic and social reform 1949-1952, the position of the social and economic reforms in Baghdad, the position of the November uprising in 1952). The study relied on an important range of sources, books, documentaries Arabic and translated along with a number of Dissertations and Thesis university as well as the large numbers of daily vigilance benefit both of which were within the period laid